Human Footprint and Forest Disturbance Reduce Space Use of Brown Bears (Ursus arctos) Across Europe - Hertel, Anne G (Global change biology, 2025)
© 2025 The Author(s). Global Change Biology published by John Wiley & Sons Ltd.